Finance for executives : - Hawawini, Gabriel A (Thomson/South-Western, 2007)
FINANCE FOR EXECUTIVES: MANAGING FOR VALUE CREATION, 3e is ideal for the future manager or experienced executive who recognizes the importance of using financial information to maximize firm value. Respected authors Gabriel Hawawini and Claude Viallet have translated their wealth of experience into a concise, analytically sound introduction to financial management that is neither too simplistic nor too theoretical. Based on modern finance principles, the book presents the most recent financial data and latest references with a level of practicality and rigorous analysis appropriate for today's experienced executive - without complicated formulas that have no direct application to decision making. Each chapter is self-contained - providing ultimate flexibility for teaching and making the book an excellent source for reference or self-learning beyond the traditional classroom. This book is perfect for executive education, executive MBA courses, or any course where you want to translate theory into practice or use a case approach. A strong problem-scenario approach presents concepts within the context of financial management problems that executives commonly face. In addition, consistent case studies analyze the same set of companies throughout the text to provide a common thread that reinforces learning